2023
DOI: 10.1002/advs.202301814
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Nano‐Theranostic Platform Based on Dual‐microRNAs Guided Self‐Feedback Tetrahedral Entropy‐Driven DNA Circuit

Abstract: MicroRNAs (miRNAs) can act as oncogenes or tumor suppressors, capable of up or down‐regulating gene expression during tumorigenesis; they are diagnostic biomarkers or therapeutic targets for tumors. To detect low abundance of intracellular oncogenic miRNAs (onco‐miRNAs) and realize synergistic gene therapy of onco‐miRNAs and tumor suppressors, a smart nano‐theranostic platform based on dual‐miRNAs guided self‐feedback tetrahedral entropy‐driven DNA circuit is created. The platform as a delivery vehicle is a DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…However, integration of logic gates as circuits into a single substrate have not been used in an intracellular environment yet. Instead, our literature study has revealed two distinct architectural approaches: i) the integration of DNA logic gates within a single DNA substrate, where gate‐to‐gate communication occurred, is absent in vitro studies; [11,41,42,81–86] and ii) the interaction and regulatory behavior of DNA logic gates localized on separate substrates has been proposed [79,87] …”
Section: Biological Applications Of Dna Icsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, integration of logic gates as circuits into a single substrate have not been used in an intracellular environment yet. Instead, our literature study has revealed two distinct architectural approaches: i) the integration of DNA logic gates within a single DNA substrate, where gate‐to‐gate communication occurred, is absent in vitro studies; [11,41,42,81–86] and ii) the interaction and regulatory behavior of DNA logic gates localized on separate substrates has been proposed [79,87] …”
Section: Biological Applications Of Dna Icsmentioning
confidence: 99%
“…Yang et al. proposed an entropy‐driven aggregation of DNA tetrahedron circuits that led to amplification of the output fluorescence signal and improved LOD from nM to fM range [79] . Therefore, further exploration of in vitro DNA ICs can be done using these 3D DNA substrates.…”
Section: Biological Applications Of Dna Icsmentioning
confidence: 99%
“…It also provides a facile and versatile strategy for the detection of other biomarkers in living cells. As shown in Figure 1D, [27] Yang et al established a smart nanoplatform based on a self-feedback tetrahedral entropy-driven DNA circuit guided by dual miRNAs. MiRNA-155 binds to sites 5* and 6* on the tetrahedron, allowing the W strand and miRNA-122 to be released from the tetrahedron and triggering the further entropy-driven reactions.…”
Section: Entropy-driven Circuit (Edc)-based Biosensorsmentioning
confidence: 99%
“…The high predictability and hybridization fidelity of DNA makes it possible to design DNAbased circuits with emergent properties and functions. [25][26][27][28][29] There have been some explorations on the immobilization of circuit elements on DNA-encoded origami scaffolds, [30][31][32] dedicated to the orienting of multi-step reactions within a confined volume. Such circuitry written into DNA origami forms a benchmark for the construction of synthetic biocircuits.…”
Section: Introductionmentioning
confidence: 99%